2021
DOI: 10.3390/insects12111017
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Effect of Zinc Oxide Nanoparticles against Spodoptera frugiperda under Laboratory Conditions

Abstract: Fall armyworm Spodoptera frugiperda is a major pest of corn, rice, and sorghum among other crops usually controlled using synthetic or biological insecticides. Currently, the new invention of nanotechnology is taking root in the agricultural industry as an alternative source of pest management that is target-specific, safe, and efficient. This study sought to determine the efficacy of commercial Zinc Oxide (ZnO) nanoparticles (NPs) towards S. frugiperda under laboratory conditions. ZnO NPs were diluted into di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…This indicated that HNTs have a controlled release effect toward CAP on foliar surfaces. A previous study showed mortality of about 40% of larvae after 10 days of feeding on baby corn dipped in ZnO nanoparticle solution . In contrast, HNTs are inexpensive nanomaterials and significantly increase larval mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that HNTs have a controlled release effect toward CAP on foliar surfaces. A previous study showed mortality of about 40% of larvae after 10 days of feeding on baby corn dipped in ZnO nanoparticle solution . In contrast, HNTs are inexpensive nanomaterials and significantly increase larval mortality.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed mortality of about 40% of larvae after 10 days of feeding on baby corn dipped in ZnO nanoparticle solution. 44 In contrast, HNTs are inexpensive nanomaterials and significantly increase larval mortality. HNTs demonstrate a promising potential to be used as an alternative to the more lethal insecticides in controlling S. f rugiperda and other species.…”
Section: Foliar Adhesion and Washout Resistance Of Hnts−cap Emulsionsmentioning
confidence: 99%
“…The decrease in adult longevity (especially oviposition period) of M. domestica obtained by the treatment with the tested NPs might be due to their accumulation in the different developmental stages. The efficiency of ZnONPs was also demonstrated against Spodoptera frugiperda at various doses (100-500 ppm), and adverse effects on development and the number of days required for the insect to finish its life cycle were reported [42] .…”
Section: Discussionmentioning
confidence: 97%
“…Khooshe-Bast et al (2016) tested ZnO-NPs on Trialeurodes vaporariorum, the LC50 value was 7.35 mg and the mortality rate was 91.6% at 20 mg. Ramadan et al (2020) reported that the latent biological responses of Schistocerca gregaria treated with ZnO were more than that of CuO-NPs. Pittarate et al (2021) and Eskin & Nurullahoğlu (2022) also concluded that ZnO-NPs have toxic effects on Spodoptera frugiperda and Galleria mellonella. Other authors reported the toxic effects of CuO-NPs against different mosquito species (Vivekanandhan et al 2021a, b) and Spodoptera frugiperda (Rahman et al, 2022).…”
Section: Tablementioning
confidence: 99%
“…Zinc oxide NPs are popular among the significant metal oxides due to their physical and chemical peculiarity (Khooshe-Bast et al, 2016). ZnO-NPs have proved to possess enormous potential against insect pests (Haroun et al, 2020 andPittarate et al, 2021). The development of Nano-pesticides derived from Copper and Copper oxide has received considerable attention in the pesticide industry in recent years (Benilli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%